2015
DOI: 10.1249/mss.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Function and Muscle Deoxygenation Dynamics during Ramp Exercise in Children

Abstract: The sex difference in peak V˙O2 in 9- to 10-yr-old children is, in part, related to sex-specific changes in muscle O2 extraction dynamics during incremental exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 43 publications
7
42
1
Order By: Relevance
“…A poorer matching of muscle oxygen delivery to oxygen utilization in girls was reported in a study that used near-infrared spectroscopy to measure microcirculatory changes in deoxygenated hemoglobin and myoglobin. The authors concluded that this phenomenon may contribute to girls' lower peakVO 2 (28). However, although the physiologic mechanisms underlying sex differences in youth aerobic fitness are emerging, they have yet to be fully elucidated (5).…”
Section: Discussionmentioning
confidence: 99%
“…A poorer matching of muscle oxygen delivery to oxygen utilization in girls was reported in a study that used near-infrared spectroscopy to measure microcirculatory changes in deoxygenated hemoglobin and myoglobin. The authors concluded that this phenomenon may contribute to girls' lower peakVO 2 (28). However, although the physiologic mechanisms underlying sex differences in youth aerobic fitness are emerging, they have yet to be fully elucidated (5).…”
Section: Discussionmentioning
confidence: 99%
“…Boys’ peak VO 2 may be further supplemented by an increase in blood haemoglobin concentration during late teens 73–75. The prepubertal sex difference in peak VO 2 has been attributed to boys’ greater stroke index,76–78 boys’ higher maximal arterial-venous oxygen difference79 and differences in the balance between oxygen delivery to and utilisation in the muscles 80…”
Section: Maximal (Or Peak) Aerobic and Anaerobic Performancementioning
confidence: 99%
“…Although peak aerobic fitness significantly increased, in line with Baquet et al (2001), GET appeared to be unaffected by the HIIT intervention for both those with and without asthma, suggesting that training above the GET for short intermittent periods may not elicit improvements. The GET%V̇O2 were similar at baseline to previous studies (McNarry et al, 2015a), however, contrary to HIIT in normal weight children (McNarry et al, 2015b), GET significantly increased in both intervention and control groups within the present study. This suggest that increases in GET are possibly due to the maturational changes in both those in the intervention and control during a period of rapid growth that may have occurred during that time (Breese et al, 2010), although a larger study is required to confirm this suggestion.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, techniques to investigate changes in O2 delivery and muscle blood flow were costly, invasive and not ethically sound for use in paediatric populations, for example muscle biopsy, tissue O2 microelectrodes and myoglobin O2 saturation by spectrophotometric analysis. NIRS is used in recent research (McNarry et al, 2015a and the current thesis as it is relatively cheap, portable, non-invasive and most importantly provides a continuous measure to provide measures of the dynamic changes in tissue oxygenation.…”
Section: Oxygen Uptake Kineticsmentioning
confidence: 99%